ANALISIS SENSITIVITAS PARAMETER HIDROLOGI, SEDIMENTASI DAN HARA DENGAN MENGGUNAKAN MODEL AGNPS UNTUK PENGELOLAAN LINGKUNGAN - Nugroho, Sutopo Purwo (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2000)
In Indonesia, the serious problems of degradation water quality from nonpoint source pollution was not yet many applied on watershed. Agricultural activities such as cultivation and application of fertilizer and pesticide will influence water quality, with activities in runoff-producing zones and near streams having a greater effect than those elsewhere. Water quality integrates all sources of pollutants. Nonpoint sources, by definition, are diffuse and not easily identified or quantified. The control technologies and best management practice available are generally expensive to beimplemented. AGNPS model is a model hydrology that should used to identify and quantify the nonpoint source pollution from watershed. The AGNPS is an event-based model that simulates surface runoff, sediment, and nutrient transport primarily from agricultural watersheds. In addition, the model considers point sources of water, sediment, nutrients, and chemical oxigen demand (COD) from animal feedlots, and spring. The model has the ability to output water quality characteristics at intermediate points throughout the watershed network. Seven parameters were selected out of twenty two parameters based on their significance in sensitivity to hydrology, erosion and sediment, and nutrient yield output. That seven parameters consist of SCS curve number, Manning’s roughness coefficient, cover and management factor, land slope, channel sideslope, practice factor and fertilization availability factor. Omitted parameters in the hypothetical scenario formulation were either parameters of uncontrollable nature such as rainfall, EI30, soil erodibility, or parameters that had least significant sensitivity such as field slope length and channel slope. The simulation with BMP system has been conducted from the parameter adjustment for seven parameters. The BMP scenario was mosteffective in reducing the degree of volume and peak runoff rate by 32,08% and 29,66% from the base value of 0,53 inches and 118,51 cfs. All erosion and sediment related nonpoint source pollutants were significantly reduced by 66,36% from the base value of 135,67 tons by altering the cover and management factor (C-factor) and the practice factor (P-factor). At the time that, total N dan total P were significantly reduced by 56,85% and 57,92% from the base value of 11,15 lbs/acre and 7,01 lbs/acre with that same of methods.